Do chronological age and selected socio-demographic factors affect quality of life in females with breast cancer? - Skrzypczak, Magdalena; Łaski, Piotr; Czerniak, Urszula; Kycler, Witold (Anthropological Review, 2009)
The main aim of this study is to determine whether chronological age and selected socio-demographic factors affect quality of life in females with breast cancer. The sample group consisted of 145 females between 32.0 and 84.4 years of age, after radical surgery treatment, chemotherapy, radiotherapy and undergoing hormonotherapy. The results indicate no significant differences between individuals varied by chronological age, and by place of residence. The time elapsed since the diagnosis was a significant differentiating factor in terms of the self-reported extent of positive emotions, cognitive problems and sexual functioning. Higher educated females were more inclined to social avoidance and more severely affected by fatigue - those with partners more so than single ones. The distress related to the disease and its treatment degrades the patients' quality of life so severely that other factors, such as socio-demographic, chronological age or period since diagnosis, do not play as an important role in a subjective evaluation of quality of life. One needs to be cognizant of the variety of coexisting factors, including psychological and characterological, that contribute to the quality of life evaluation.